2020
DOI: 10.3390/ijerph17217717
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Emotional Intelligence, Cybervictimization, and Academic Performance in Secondary School Students

Abstract: The benefits attributed to emotional intelligence (EI) in a school environment can be observed in areas such as interpersonal relationships, psychological well-being, academic performance, and avoidance of disruptive behaviors. The objective of this study was to analyze a sample of 3451 adolescents from a secondary school to test whether EI is a protector against cybervictimization and the repercussions of cybervictimization, and whether EI has an influence on academic performance. The instruments used in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 72 publications
1
16
1
6
Order By: Relevance
“…These results are in line with proposals that there is a strong relationship between bullying and achievement and commitment to study (Gardella et al, 2017;Zhao and Yu, 2020;Yu and Zhao, 2021). At this point, it is worth recalling the need for training on emotional intelligence to mediate these effects (Martínez-Martínez et al, 2020;Cañas et al, 2020a).…”
Section: Relationship Between the Latent Factorssupporting
confidence: 88%
See 1 more Smart Citation
“…These results are in line with proposals that there is a strong relationship between bullying and achievement and commitment to study (Gardella et al, 2017;Zhao and Yu, 2020;Yu and Zhao, 2021). At this point, it is worth recalling the need for training on emotional intelligence to mediate these effects (Martínez-Martínez et al, 2020;Cañas et al, 2020a).…”
Section: Relationship Between the Latent Factorssupporting
confidence: 88%
“…At this point, it is necessary to highlight the mediating role of emotional intelligence between academic performance and bullying (Martínez-Martínez et al, 2020). In a study conducted by these authors, students suffering cyberbullying showed low emotional intelligence but did not always show low academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Research literature suggests that emotionally intelligent people report better psychological adjustment (e.g., self-esteem, happiness, optimism, social support, and less depression; Lopez-Zafra et al, 2019;Tejada-Gallardo et al, 2020) as well as higher levels of life satisfaction, well-being, and flourishing (Sánchez-Álvarez et al, 2016;Callea et al, 2019;Lopez-Zafra et al, 2019;Salavera et al, 2020). In educational context, previous findings suggest that developing emotional competences may be a useful resource to increase the levels of flourishing and improve psychological adjustment and interpersonal relationships in adolescent population (Rey et al, 2019;Trigueros et al, 2019;Martínez-Martínez et al, 2020). Furthermore, evidence shows that emotional intelligence is moderately associated with students' academic performance (MacCann et al, 2020;Sánchez-Álvarez et al, 2020).…”
Section: Emotional Intelligence and Academic Performancementioning
confidence: 98%
“…Regarding the relationship between cyberbullying and academic performance, the literature review shows inconclusive results. While most studies have concluded that there is a negative association between cyberbullying and academic performance [33][34][35], others note that the relationship is not significant and that the impact of traditional social-type bullying on academic performance is greater [36]. Thus, the study developed by [33], with 3451 Spanish students aged 12 to 19 years, concluded that young people with lower emotional intelligence were more likely to suffer cyberbullying and could experience negative repercussions on their school success with poor academic performance.…”
Section: Cyberbullying and Academic Performancementioning
confidence: 99%
“…While most studies have concluded that there is a negative association between cyberbullying and academic performance [33][34][35], others note that the relationship is not significant and that the impact of traditional social-type bullying on academic performance is greater [36]. Thus, the study developed by [33], with 3451 Spanish students aged 12 to 19 years, concluded that young people with lower emotional intelligence were more likely to suffer cyberbullying and could experience negative repercussions on their school success with poor academic performance. Okumu et al [34], with a representative sample of U.S. university students, concluded that cyberbullying is associated with poor academic performance.…”
Section: Cyberbullying and Academic Performancementioning
confidence: 99%